PREOPERATIVE EXAMINATION OF PATIENTS WITH ANTERIOR-INFERIOR AND INFERIOR HABITUAL SHOULDER DISLOCATION - YuV V Larteev; VV V Kobzarev (Наука и инновации в медицине, 2017)
Aim - to determine a rational method for the treatment of patients with anterior-inferior and inferior habitual shoulder dislocation based on the results of examination of patients. Material and methods. The study involved analysis of the treatment results of 98 patients with anterior-inferior and inferior chronic instability of the shoulder joint. Patients were divided into two clinical groups. The first group consisted of 52 patients, and the choice of treatment was based only on the diagnosis and did not take into account the peculiarities of pathology in each particular patient, which led to unsatisfactory results. To improve the results of treatment of patients with anterior-inferior and inferior chronic instability of the shoulder joint, a set of diagnostic measures was proposed, which made it possible to choose the proper method and volume of intervention taking into account the direction of the dislocation and the plane ofjoint displacement. The second clinical group consisted of 46 patients who underwent examination and treatment according to the proposed complex. A detailed description of the proposed diagnostic complex is presented, including a number of clinical and instrumental methods for examining patients, and a self-administered questionnaire for the patients. Based on the results of the survey, taking into account the direction of the dislocation, the patients underwent surgical intervention, which made it possible to achieve stability of the joint and restore the function of the limb. Conclusion. The choice of optimal diagnostic complex with regard to the direction of dislocation and the plane of shoulder head displacement in habitual shoulder dislocation helps to choose pathogenically justified surgical method and contributes to the full functional restoration of the limb.